Virological failure and antiretroviral resistance among HIV-infected children after five years follow-up in the ANRS 12225-PEDIACAM cohort in Cameroon. - Paul Alain Tagnouokam-Ngoupo; Ida Calixte Penda; Jules Brice Tchatchueng Mbougua; Suzie Tetang Ndiang; Francis Yuya Septoh; Angeladine Kenne; Jeannine Eboumbou Ngallè; Sorel Jakpou; Francis Ateba Ndongo; Josiane Warszawski; Albert Faye; Mathurin Cyrille Tejiokem; et al. (PLoS ONE)
Objective In the present study, we aimed to evaluate the virological failure (VF) and drug resistance among treated HIV-infected children after five years follow-up in the ANRS-Pediacam cohort in Cameroon. Methods From November 2007 to October 2011, HIV-infected children born to HIV-infected mothers were included in the ANRS-PEDIACAM study and followed-up for more than 5 years. Plasma viral load (VL) was measured at each visit (every three months until month 24 and every 6 months thereafter). VF was the main outcome and HIV drug resistance test was performed using the ANRS procedures and algorithm. Results Data from 155 children were analyzed. The median age at combination antiretroviral therapy (cART) initiation was 4.2 months (interquartile range (IQR): 3.2-5.8), with 103 (66.5%) children taking LPV/r-containing regimen and 51 (32.9%) children taking NVP. After five years follow-up, 63 (40.6%; CI: 32.9-48.8) children experienced VF. The median duration between cART initiation and VF was 22.1 months (IQR: 11.9-37.1) with a median VL of 4.8 log10 (IQR: 4.0-5.5). Among the 57 children with HIV drug resistance results, 40 (70.2%) had at least one drug resistance mutation. The highest resistance rates (30.4-66.1%) were obtained with Lamivudine; Efavirenz; Nevirapine and Rilpivirine. Conclusions These results show high resistance to NNRTI and emphasize the need of VL and resistance tests for optimal follow-up of HIV-infected people especially children.